CTL Learning Model Development In Fiqh Subjects At KH Siddiq Ma’arif Elementary School Of Jember - Rosady, Imron; Dahlan, Moh.; Ubaidillah, Ubaidillah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
This paper describes the development CTL learning model in Fiqh subjects astheoretically and practically it is a learning model that has been tested for validity, practicality, and effectiveness, so that it can be considered as a learning model. CTLexplains about achieving the learning objectives, namely the main point is to increase students’ thinking level, the presentation of material in worksheets must be arranged according to students’ thinking level, teaching and learning activities must follow the phases of learning orientation, group discussions, class discussions, integration, and evaluation as learning syntax, in addition to the pre-test and post-test. As a results, CTLhas contributed to learning theory. The CTL is a prescriptive learning theory, which means that it prescribes optimal learning to achieve learning outcomes (especially to increase students’ thinking level). The question theory is that “to level up students’ thinking level in Fiqh subjects is by arranging learning materials according to students’abilities and the implementation of CTL.